Analysis of the Advantage of Respondents Formulation of Liniment Aromaterapy of Essential Oil Syzygium Aromaticum L - Ariyanti Ariyanti; Eni Masruriati; Arini Asna Hidayah; Mazikhatul Azka (Global Health Science Group, 2020)
Syzygium aromaticum L.'s essential oil aromatherapy liniment formula is one of the external medicinal preparations used to relieve rubbing, massage and massage as well as relieving muscle and joint pain. Utilization of Syzygium aromaticum L. essential oil as a provider of active ingredients that can provide natural fragrance, sedative and analgesic effects in the liniment formula. This study aims to obtain the aromatherapy liniment formulation of Syzygium aromaticum L. essential oil so that the wind oil formula that is preferred by respondents and meets the requirements of traditional medicine is obtained. The experimental research the post test only controlled group design. The study was divided into 2 groups, namely the control group and the treatment group, namely the aromatherapy liniment formulation of Syzygium aromaticum L. essential oil with a concentration of 2.5% v / v, 5% v / v, 7.5% v / v, and control. Testing, organoleptic test, irritation test, pH stability test and respondent preference test. The results showed that the overall results of the Respoden's Preference test on the aromatherapy liniment of Syzygium aromaticum L. essential oil showed that consumers preferred the product at a concentration of 7.5% v / v.